2010
DOI: 10.4049/jimmunol.0902723
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Delayed-Type Hypersensitivity Responses by Mesenchymal Stem Cells Is Associated with Bystander T Cell Apoptosis in the Draining Lymph Node

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…As haptens are not immunogenic by themselves but able to elicit immune responses only when binding to a protein, they have been frequently used as the most suitable allergen substitute to reproduce human disease. Lim and colleagues reported that IV infused BMSCs alleviated the murine CHS through the NO-mediated induction of activated T cell apoptosis in the dLNs [70]. In addition, Su et al demonstrated that IV administration of human gingiva-derived MSCs (hGMSCs) significantly attenuated the symptoms of murine CHS to a similar extent in the BMSCs-injected group.…”
Section: Preclinical and Clinical Studies Of Mscs In Inflammatory mentioning
confidence: 99%
“…As haptens are not immunogenic by themselves but able to elicit immune responses only when binding to a protein, they have been frequently used as the most suitable allergen substitute to reproduce human disease. Lim and colleagues reported that IV infused BMSCs alleviated the murine CHS through the NO-mediated induction of activated T cell apoptosis in the dLNs [70]. In addition, Su et al demonstrated that IV administration of human gingiva-derived MSCs (hGMSCs) significantly attenuated the symptoms of murine CHS to a similar extent in the BMSCs-injected group.…”
Section: Preclinical and Clinical Studies Of Mscs In Inflammatory mentioning
confidence: 99%
“…The abundance of mediators identified to date suggests that MSCs exploit different immunosuppressive mechanisms under different disease conditions. MSC therapy has been successful in a range of disease models and some clinical conditions known to be associated with damaging effector T-cell responses or failure of T reg -mediated counter-regulation or both [4,6,8,11,22,25-28]. Overall, it is now very well established that MSCs exert diverse and potent modulatory effects on the T-cell compartment of the immune system, most of which are suppressive in nature and of potential therapeutic value.…”
Section: An Introduction To Mesenchymal Stem Cell Modulation Of T Celmentioning
confidence: 99%
“…Recently, we published that small, but significant numbers of mouse MSCs infused i.v. to the mice localized at the cortical area of the lymph nodes, in particular, in the draining lymph nodes and induced apoptosis of the activated T cells [27]. In those studies, we found that some of infused MSCs directly contact T cells, dendritic cells, B cells, and possibly Treg cells, but they only exerted apoptotic effects on the activated T cells.…”
Section: Discussionmentioning
confidence: 92%